2016
DOI: 10.1016/j.immuni.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Fine Particles Induce Alveolar Macrophage Death and Interleukin-1α Release to Promote Inducible Bronchus-Associated Lymphoid Tissue Formation

Abstract: Particulate pollution is thought to function as an adjuvant that can induce allergic responses. However, the exact cell types and immunological factors that initiate the lung-specific immune responses are unclear. We found that upon intratracheal instillation, particulates such as aluminum salts and silica killed alveolar macrophages (AMs), which then released interleukin-1α (IL-1α) and caused inducible bronchus-associated lymphoid tissue (iBALT) formation in the lung. IL-1α release continued for up to 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 51 publications
9
128
1
Order By: Relevance
“…Indeed, BMDMs from Mrc1 −/− mice or BMDMs with Mrc1 knockdown mice displayed altered responses to M1 and M2 stimuli, suggesting that Mrc1 and miR-511-3p control macrophage polarization and activation, which might contribute to the protection of allergen-induced inflammatory responses. 45 However, although BMDMs are broadly used surrogates for analysis of macrophage polarization, it will be essential to validate these findings in cultured alveolar macrophages ( in vitro –differentiated alveolar macrophages) 46 and human lung macrophages. Intriguingly, we found that plasma levels of miR-511-3p were significantly lower in asthmatic patients compared with those in nonasthmatic subjects, regardless of allergic status, indicating that miR-511-3p can protect against asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, BMDMs from Mrc1 −/− mice or BMDMs with Mrc1 knockdown mice displayed altered responses to M1 and M2 stimuli, suggesting that Mrc1 and miR-511-3p control macrophage polarization and activation, which might contribute to the protection of allergen-induced inflammatory responses. 45 However, although BMDMs are broadly used surrogates for analysis of macrophage polarization, it will be essential to validate these findings in cultured alveolar macrophages ( in vitro –differentiated alveolar macrophages) 46 and human lung macrophages. Intriguingly, we found that plasma levels of miR-511-3p were significantly lower in asthmatic patients compared with those in nonasthmatic subjects, regardless of allergic status, indicating that miR-511-3p can protect against asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of iSALT formation remains unknown. CD11c‐positive alveolar macrophages are suggested to play a role in organizing iBALT through interleukin (IL)‐1α release . It has been also suggested that M1 macrophages activate medial vascular smooth muscle cells to organize adventitial TLO in a murine model of atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…Alum promotes the production of PGE2 in macrophages via inflammasome‐independent mechanisms favoring IgE production . More recently, it has been shown that aluminum salts kill alveolar macrophages, which subsequently release IL‐1α promoting the formation of tertiary lymphoid tissues in the lung that sustain type‐2 allergic immune responses after allergen exposure . Many different immunopotentiators have been analyzed in mouse models of allergy.…”
Section: Allergen‐specific Immunotherapymentioning
confidence: 99%